Intelligent Routing Algorithms Assess Mobile Network - Monfared, Mohsen Davoudi; Zeinali, Shadie (International Journal of Computer Sciences and Engineering, 2025)
The use of wireless networks is widely increasing. One of these networks, ad hoc mobile networks (Mobile ad hoc networks) is. Mobile Ad hoc Network known as network short-lived. Nature-inspired algorithms (swarm intelligence) such as ant nest optimization algorithms and genetic algorithms to solve the routing problem in recent years have introduced mobile-specific networks.